SYNTHESIS, CRYSTAL STRUCTURE AND MAGNETIC PROPERTIES OF A DINUCLEAR NICKEL(II) COMPLEX WITH 3-[(1E)-N-HYDROXYETHANIMIDOYL]-4-METHYL-1H-PYRAZOLE-5-CARBOXYLIC ACID: UDC 546.74: 538 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2009)
The complex [Ni2(PzOxCA–2Н)2(Py)4]·2Н2О based on novel pyrazolate ligand 3-[(1E)-N-hydroxyethanimidoyl]-4-methyl-1H-pyrazole-5-carboxylic acid (PzOxCA) has been synthesized and its crystal structure has been determined by X-ray single crystal analysis. Magnetic susceptibility measurements in the temperature range 1.8 – 300 K revealed antiferromagnetic exchange coupling between nickel(II) ions (J = –15,23 cm–1).
Keywords: -